Detection of blacTX-M gene in Escherichia coli Isolates and Study the correlation between Biofilm formation and Antibiotic Resistance - Abbood, Daniah Saadi; Al-Sammarraie, Hanan Waleed Muhamed; Abdulhadi, Tiba Saddam (American Journal of Biology and Natural Sciences, 2025)
Urinary tract infections (UTIs) are one of the most common bacterial infection, Escherichia coli is the predominant uropathogen. Bacterial strains with biofilm-forming ability become persistent in a body and antibiotic treatment susceptible to chronic infection, for which the eradication is quite difficult. The correlation between biofilm formation and antibiotic resistance in E. coli isolated from urine samples was studied, and the blaCTX-M gene as an extended spectrum β-lactamase (ESBL) marker was identified. A total of 320 urine samples were obtained from patients attending Azadi and Kirkuk Teaching Hospitals from April to September 2024. The causative E. coli species were identified by routine microbiological techniques and VITEK2. Biofilm formation was tested by Congo Red Agar assay, whereas antimicrobial susceptibility was performed following Kirby-Bauer disc diffusion method. The blaCTX-M gene was identified by PCR. In 320 urine samples, 154 (48.1%) were culture positive; isolates of Escherichia coli numbered 138 (89.6%). One hundred and one isolates (73.2%) were found to be biofilm producers, of strong, moderate and weak producer 25.4%, 30.4% and 17.4% respectively. High production of biofilms showed the highest rates of resistance against β-lactams, Trimethoprim and Gentamicin, whereas being non-biofilm producer had lower rates. PCR analysis showed the presence of blaCTX-M gene in all isolates 100% implying ESBL associated resistance. Biofilm production by E. coli has a significant relationship with MDR especially towards β-lactams and Trimethoprim. Also, the presence of the blaCTX-M gene supports the high rate of ESBL-producing strains. Inhibition of biofilm production could improve the antibiotic effectiveness in UTI treatment.